2022
DOI: 10.1108/jme-05-2022-0065
|View full text |Cite
|
Sign up to set email alerts
|

Development model of gender socialization: school textbooks gender analysis in Georgia

Abstract: Purpose This study aims to explore gender equality in school textbooks in Georgia. Design/methodology/approach The research had the following questions: To what extent are women and men visible and represented equally in school textbooks? How do school textbooks promote gender socialization of boys and girls to be treated equally in terms of power and privileges, superiority and inferiority? Do school textbooks promote critical thinking and analysis of gender issues and problems? The content analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Education serves as a means to disrupt these norms, allowing women to express their preferences more freely in choosing life partners. This theory resonates with the socio-cultural dynamics of Malakand Division (Tabatadze and Gorgadze, 2023).…”
Section: Gender and Socialization Theorymentioning
confidence: 58%
“…Education serves as a means to disrupt these norms, allowing women to express their preferences more freely in choosing life partners. This theory resonates with the socio-cultural dynamics of Malakand Division (Tabatadze and Gorgadze, 2023).…”
Section: Gender and Socialization Theorymentioning
confidence: 58%
“…The study showed that the reviewed textbooks do not provide opportunities for discussion of gender equality and gender sensitivity issues, even though these books play an essential role in shaping attitudes and social images (Kobia, 2009). School textbooks are necessary to develop and transmit cultural values (Mkuchu, 2004) and develop positive and negative images of different sources of cultural identity (Tabatadze et al, 2013). School textbook authors do not use this power properly.…”
Section: Discussionmentioning
confidence: 99%
“…The second generation of the National Curriculum was adopted in 2011 and implemented in schools in 2011-2016, and finally, the third wave of curricular reform began in 2016. The textbooks for primary grades (1-6) were developed in 2018, and those for Basic Education (Grades 7-9) began to be developed in 2019-2021 (Tabatadze et al, 2020;Tabatadze & Gorgadze, 2022).…”
Section: Situating the Study: School Textbook Analytical Studies In G...mentioning
confidence: 99%
See 1 more Smart Citation